2018
DOI: 10.1093/carcin/bgy040
|View full text |Cite
|
Sign up to set email alerts
|

The molecular landscape of synchronous colorectal cancer reveals genetic heterogeneity

Abstract: Synchronous colorectal cancers (syCRCs), which present two or more lesions at diagnosis, are rare and pose a great challenge for clinical management. Although some predisposing factors associated with syCRCs have been studied with limited accession, the full repertoire of genomic events among the lesions within an individual and the causes of syCRCs remain unclear. We performed whole-exome sequencing of 40 surgical tumour samples of paired lesions from 20 patients to characterize the genetic alterations. Lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 43 publications
5
34
0
Order By: Relevance
“…8,[13][14][15] Thus far, there has been only a few exome-wide studies on SCRC and one study including whole-genome sequencing data of a SCRC case. [16][17][18][19] In general, these studies have supported the idea of independent origins of synchronous tumours. Another hypothesis underlying SCRC, in addition to a common progenitor, is the field effect.…”
Section: Introductionsupporting
confidence: 65%
“…8,[13][14][15] Thus far, there has been only a few exome-wide studies on SCRC and one study including whole-genome sequencing data of a SCRC case. [16][17][18][19] In general, these studies have supported the idea of independent origins of synchronous tumours. Another hypothesis underlying SCRC, in addition to a common progenitor, is the field effect.…”
Section: Introductionsupporting
confidence: 65%
“…In patient C, this shared mutation could either suggest a common tumour origin or is a striking example of convergent evolution in tumour development, likely arising via the serrated BRAF pathway from sessile serrated polyp precursors. However, overall our results suggest syCRCs have a tendency to originate independently, while often accessing the same mutational processes 29,30,32 . In terms of the temporal development of the tumours, for the older patients B (79 years of age) and C (70 years of age) there are no records of prior endoscopy or biopsies prior to the index admission.…”
Section: Discussionmentioning
confidence: 61%
“…Predisposing known genetic conditions are causative for about only 10% of syCRCs 27 , suggesting that other genetic and environmental risk factors are involved. Previous studies on syCRCs have reported high heterogeneity of variants between synchronous tumours, with distinct mutations occurring in known CRC genes, and variation between tumour signature content, immune cell scores and MSI status [29][30][31][32] . Although prognosis of syCRC patients does not seem to vary significantly from that of solitary CRC patients 30,33 , an understanding of the mechanisms implicated in this phenomenon is still limited and no specific guidelines are currently available for the management and treatment of synchronous cases.…”
Section: Introductionmentioning
confidence: 99%
“…However, this is not supported by previous studies that showed distinct molecular profiles in synchronous and metachronous tumors, nor is it supported by the distinct molecular profiles that we observed in our control group (Table 3). 13,14 Moreover, the experiments conducted do not exclude possibilities of tumor transmission other than working channel contamination, such as exfoliation of cancer cells passively being taken up into biopsied or polypectomy site tissue. 7 Studies on tumor regrowth based on exfoliated cells performed in rats showed that colon cancer cells have the ability to regrow on damaged mucosa in a minority of cases, whereas an intact mucosa was seen to be completely resistant.…”
Section: Discussionmentioning
confidence: 99%